PENGEMBANGAN VIDEO PEMBELAJARAN PADA MATERI SISTEM ORGANISASI KEHIDUPAN MAKHLUK HIDUP TINGKAT SMP - Yuliana Bili; Hasminar Rachman Fidiastuti; Yuswa Istikomayanti (Inteligensi : Jurnal Ilmu Pendidikan, 2022)
The aim of this research was to produce learning videos on the material of the life organization systems of living things as learning material for class VII junior high school students. This research was development research with Research and Development, where the product developed will be assessed and validated by media and materials experts and tested on 24 class VII middle school students. Data from the results of questionnaire analysis by calculating the percentage of achievement in each component, namely 87.5% (media expert), 90% (linguist expert), and 74% (material expert) and the teacher assessment results were 79% with the category suitable for use. Meanwhile, data from the results of the analysis of student response questionnaires calculated the average percentage of 86.83% in the very feasible category. From these data it can be concluded that video-based learning media is appropriate and students agree to use it as a learning media to support the teaching and learning process in material on the organization of living things for junior high school.